On the strange place of religion in contemporary art - Elkins, James, 1955- (Routledge, 2004)
For millennia, art has been religious - even in times and places when there was no word for 'art'. Then, in the Renaissance, it became possible for art to glorify the artist, making viewers think more of his skills than of the subjects he portrayed. The modern artist faces a more complex dilemma - one that no art historian has talked about until now. Can contemporary art say anything about spirituality? Is contemporary art is spiritual? What might it mean to say that the art you make expresses your spiritual belief?The Impossibility of Transcendence is about the curious disconnect between spir.